2012
DOI: 10.1007/s00259-012-2187-8
|View full text |Cite
|
Sign up to set email alerts
|

123I-Labelled metaiodobenzylguanidine for the evaluation of cardiac sympathetic denervation in early stage amyloidosis

Abstract: PurposeCardiac amyloidosis is a rare disorder, but it may lead to potentially life-threatening restrictive cardiomyopathy. Cardiac manifestations frequently occur in primary amyloidosis (AL) and familial amyloidosis (ATTR), but are uncommon in secondary amyloidosis (AA). Echocardiography is the method of choice for assessing cardiac amyloidosis. Amyloid deposits impair the function of sympathetic nerve endings. Disturbance of myocardial sympathetic innervations may play an important role in the remodelling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…The author concluded that 123 I-MIBG scintigraphy can detect cardiac denervation in ATTRm patients before signs of amyloidosis on echocardiogram. 37 The early detection of cardiac denervation with 123 I-MIBG in ATTRm FAP is important as sympathetic denervation occurs early in the disease and all current therapies under investigation, including liver transplantation, 38 are aimed at preventing disease progression and not removing pre-existing amyloid.…”
Section: Methodsmentioning
confidence: 99%
“…The author concluded that 123 I-MIBG scintigraphy can detect cardiac denervation in ATTRm patients before signs of amyloidosis on echocardiogram. 37 The early detection of cardiac denervation with 123 I-MIBG in ATTRm FAP is important as sympathetic denervation occurs early in the disease and all current therapies under investigation, including liver transplantation, 38 are aimed at preventing disease progression and not removing pre-existing amyloid.…”
Section: Methodsmentioning
confidence: 99%
“…1 123 I mIBG has been shown to identify cardiac sympathetic denervation that is known to occur in the early stages of ATTR-type amyloidosis. 16 For PET imaging, the most commonly used cardiac tracers include 11 C-PIB and 18 F-florbetapir. A pilot study by Antoni and colleagues showed obvious 11 C-PIB uptake in the LV wall of all 10 patients with cardiac amyloidosis (7 AL and 3 ATTR subtypes), whereas no LV uptake was seen in any of the 5 healthy controls.…”
Section: See Related Article Pp 181-190mentioning
confidence: 99%
“…2) [9]. 123 I-metaiodobenzylguanidine ( 123 I-MIBG) scintigraphy showed an increased washout (34%) and low heart-mediastinum ratio (late uptake 1.16) indicative of cardiac denervation [10]. A fine needle subcutaneous abdominal fat aspirate yielded a TTR concentration of amyloid in fat of 658-ng/mg fat tissue (Nb7.5 ng/mg) [6,7].…”
Section: Casementioning
confidence: 99%